Electroacupuncture at Zusanli Rescues the Enteric Neuronal Loss in the Stomach of Diabetic Rats. (January 2013) - Hu, Min; Du, Fan; Liu, Shi
The purpose of this study was to investigate the effects of electroacupuncture at Zusanli acupoint on the enteric neuropathy in diabetic rats. Sprague–Dawley rats were divided into different groups depending on the total electroacupuncture span and frequency. The expression of nitric oxide synthase (nNOS), choline acetyltransferase (CHAT), protein gene product 9.5 (PGP9.5), and doublecortin was significantly decreased in the diabetic group compared with the control group. Long-term electroacupuncture at Zusanli with either high frequency or low frequency could increase the expression levels of nNOS, CHAT, PGP9.5, and doublecortin, and the increase was greater in the high-frequency group. But no obvious changes were seen in the short-term electroacupuncture groups. These results suggest that electroacupuncture at Zusanli can restore the deficiency of enteric neurons in diabetes partly but a comparative long duration of stimuli (6 weeks) is required. The increase of doublecortin may be involved in this positive process.